2019
DOI: 10.3390/rs11121506
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Coastal Dune Natural Vegetation Types Using a Phenology-Based Mapping Approach: The Potential of Sentinel-2

Abstract: Coastal areas harbor the most threatened ecosystems on Earth, and cost-effective ways to monitor and protect them are urgently needed, but they represent a challenge for habitat mapping and multi-temporal observations. The availability of open access, remotely sensed data with increasing spatial and spectral resolution is promising in this context. Thus, in a sector of the Mediterranean coast (Lazio region, Italy), we tested the strength of a phenology-based vegetation mapping approach and statistically compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 86 publications
(122 reference statements)
3
44
0
Order By: Relevance
“…Indeed, they act as a sensible and pragmatic tool to show, monitor and preview environmental changes [61]. The obtained results demonstrated that this kind of approach: (i) is cost saving, effective, accurate and could be run periodically to output maps that reflect the "current" status of vegetation and habitats also reducing costs and risks of delaying the reporting requested by the Habitats Directive (92/43/EEC) [19]; (ii) the FPCA is a suitable and elegant solution to simultaneously express the relationships between remotely sensed and ecological field data. The approach could be applied to other vegetation typologies also supporting policy makers with updated maps to monitor and preserve biodiversity with a reduced effort in terms of required resources.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Indeed, they act as a sensible and pragmatic tool to show, monitor and preview environmental changes [61]. The obtained results demonstrated that this kind of approach: (i) is cost saving, effective, accurate and could be run periodically to output maps that reflect the "current" status of vegetation and habitats also reducing costs and risks of delaying the reporting requested by the Habitats Directive (92/43/EEC) [19]; (ii) the FPCA is a suitable and elegant solution to simultaneously express the relationships between remotely sensed and ecological field data. The approach could be applied to other vegetation typologies also supporting policy makers with updated maps to monitor and preserve biodiversity with a reduced effort in terms of required resources.…”
Section: Discussionmentioning
confidence: 88%
“…The results suggest that the Mediterranean forest plant association has distinct remotely sensed phenological behaviors and that the main seasonal phenological variations, useful to discriminate the contiguous Mediterranean habitats [17,19,20], extracted from the NDVI Landsat 8 time series using FPCA, are efficacy predictors for mapping the forest plant associations. Thus, the supervised random forest classification, similarly to Zhu and Liu [55], revealed that the main remotely sensed phenological seasonal variations (expressed by the first four pixel-based FPCA scores) contributed to the high OA (87.5%) of the map, much more than the lithological and topographic features.…”
Section: Mapping Performance and Methodological Considerationsmentioning
confidence: 97%
See 1 more Smart Citation
“…The experimental results of Frison et al [32] show that radar data is more accurate for phenological estimation than optical data. Flavio et al [33] have tested the phenology-based vegetation mapping method and proved it effective. Some studies have calculated the phenological characteristics of mangroves to derive environmental driving factors that affect their growth [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of open access remotely sensed data with increasing spatial and spectral resolution is promising in this context. Thus, in a sector of the Mediterranean coast (Lazio region, Italy), Marzialetti et al [4] tested the strength of a phenology-based vegetation mapping approach and statistically compared results with previous studies, making use of open source products across all the processing chain. We identified five accurate land cover classes in three hierarchical levels, with good values of agreement with previous studies for the first and the second hierarchical levels.…”
mentioning
confidence: 99%